Benda Asing Pada Telinga "Ear Foreign Body" - Idham Lubis, Muhammad; Rumanda, Reza (Lentera : Jurnal Ilmiah Sains, Teknologi, Ekonomi, Sosial, dan Budaya, 2024)
Foreign objects in the ear canal can vary, either being inanimate or living. Foreign objects in the ear are a common case encountered in ENT emergency rooms, with the highest incidence occurring in children. This is due to their high curiosity and experimental nature at that age, though it is also found in adults. Common foreign objects include plastic beads, cotton bud tips, parts of earrings, green bean seeds, small animals, toys, erasers, batteries, and insects.In this journal report, the author describes a case involving a 10-year-old boy who visited the ENT clinic at Dr. Fauziah Hospital, Biruen, complaining of a foreign object, specifically a live animal, in his ear. He reported discomfort and pain due to the sensation of movement. An endoscopic examination revealed a white tick attached to the right ear's external auditory canal. The treatment involved irrigation with warm water to dislodge the insect. After irrigation was completed, the patient was given instructions for follow-up care and discharged